Derivational Morpheme Errors in English: A Study of Libyan Students at Al-Mergib University - Firas Fouzi Ibsheeyah; Senowarsito Senowarsito; Siti Nur’Aini (Universitas Hamzanwadi, 2023)
Proficiency in a language entail mastering components such as lexical nuances and grammatical rules. However, morphology often gets overlooked in university programs, underscoring the need for students to heighten their morphological awareness to refine their English writing. This research delves into the errors in using derivational morphemes by third- and fourth-year English major students from Libya. The objective is to identify, categorize, and understand the root causes of these errors. The study, involving ten participants from Al-Mergib University, used a qualitative research approach with essay writing as the primary data collection tool. The analysis uncovers various errors in derivational morpheme usage. Specifically, the study recorded 36 omission errors, 16 order errors, 6 incorrect formations, and 3 other errors. A striking observation was that errors predominantly centered on suffixes over prefixes. The most frequent mistakes arose in the transformation of adjectives to adverbs and verbs to nouns, encompassing omissions, additions, misordering, and misformations. For educators, this study underscores the importance of understanding student challenges with derivational morphemes, especially related to verbs and nouns. It advocates for a pedagogical approach that includes group discussions analyzing relevant texts. By highlighting these errors, the study offers valuable insights into areas where Libyan students require focused attention in English morphology.